When the former ceo stays on as board chair: effects on successor discretion, strategic change, and performance - Quigley, Timothy J.; Hambrick, Donald C. (Strategic Management Journal, 2012)
Abstract Prior research on CEO succession has omitted consideration of a critical institutional reality: some exiting CEOs do not fully depart the scene but instead remain as board chairs. We posit that predecessor retention restricts a successor's discretion, thus dampening his or her ability to make strategic changes or deliver performance that deviates from pre‐succession levels. In short, a predecessor's continuing presence suppresses a new CEO's influence. Based on analysis of 181 successions in high technology firms, and with extensive controls (for circumstances associated with succession, the firm's need and capacity for change, and for endogeneity), we find substantial support for our hypotheses. In supplementary analyses, we find that retention has a more pronounced effect in preventing a new CEO from making big performance gains than in preventing big drops. Copyright © 2011 John Wiley & Sons, Ltd.